Resolution of severe facial asymmetry caused by osteochondroma through temporomandibular joint surgery associated with bimaxillary orthognathics - Brito, Lucas Teixeira (2022)
Facial asymmetry can result from numerous types of diseases, such as: trauma (edema, emphysema, hematomas) and serious infectious processes that generate volumetric increases in the face quickly and noticeably. On the other hand, the development of cysts and tumors, changes in development/growth of both hard and soft tissues, are slower processes and consequently perceived when there is a significant change. Osteochondroma (OC), one of the intraosseous lesions can be defined as a protrusion of bone cartilage that arises from the outermost surface of the affected bone. The objective of this work is to describe a complex, but stable and satisfactory treatment methodology with good stability and satisfactory aesthetic-functional results. Discussion directly related to therapeutic modality, cost-effectiveness of localized treatment compared to combined treatment, risks, benefits and the like. The results show images that make it possible to verify the accuracy and applicability of virtual planning in the correction of deformities associated with the expertise of surgeons with great experience in surgical treatments, ending with a satisfactory result for the patient and team.